2020
DOI: 10.1371/journal.pone.0239838
|View full text |Cite
|
Sign up to set email alerts
|

Preschool environment and preschool teacher’s physical activity and their association with children’s activity levels at preschool

Abstract: The aim of this study was to investigate the association between preschool playground size, formalized physical activity (PA) policies, time spent outdoors and preschool teacher's levels of PA and children's objectively assessed levels of PA and sedentary time (ST) during preschool hours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 41 publications
1
32
0
Order By: Relevance
“…Furthermore, few previous studies have explored the association between preschool PA policies and children's PA levels (25)(26)(27). An observational study from Sweden, have demonstrated higher PA levels in children enlisted in preschools with a PA policy (27). This result is in line with ndings from other countries (25,26).…”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations
“…Furthermore, few previous studies have explored the association between preschool PA policies and children's PA levels (25)(26)(27). An observational study from Sweden, have demonstrated higher PA levels in children enlisted in preschools with a PA policy (27). This result is in line with ndings from other countries (25,26).…”
Section: Introductionsupporting
confidence: 67%
“…Although policies may be potentialy modi able organizational factors in preschools, introducing preschool policy can be challenging since preschool policies often suffer from unclearness, poor implementation, lack of tools for follow-up and measures of compliance (23,24). Furthermore, few previous studies have explored the association between preschool PA policies and children's PA levels (25)(26)(27). An observational study from Sweden, have demonstrated higher PA levels in children enlisted in preschools with a PA policy (27).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings are particularly important for ECE teachers, as previous research has found that these teachers have many health and well-being-related risks (e.g., obesity, depressive symptoms, perceived stress, [ 9 ]. Moreover, physically active ECE teachers would serve as role models and motivate children to be physically active [ 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…PA is particularly important for ECE teachers, as previous research has found that those who were more physically active were less emotionally exhausted and had less intention to leave their current position [ 19 ]. Additionally, ECE teachers serve as role models to children by helping them develop positive behaviors and attitudes toward PA [ 20 , 21 , 22 ]. National PA recommendations within the United States have been established to guide individuals toward a healthier lifestyle [ 23 ].…”
Section: Introductionmentioning
confidence: 99%